The Influence of Professionalism and Work Culture on Work Discipline Impacts Employee Performance at the Manpower and Transmigration Office of East Tanjung Jabung Regency - Asgaruddin Asgaruddin; Hapzi Ali; Maya Maria (Dinasti Publisher, 2025)
This study aims to analyze the influence of work professionalism and work culture on employee performance, both directly and indirectly through work discipline as an intervening variable at the Manpower and Transmigration Office of Tanjung Jabung Timur Regency. This study uses a quantitative approach with descriptive and verification methods. The study population was all 46 employees, and all of them were used as research samples (saturated samples). Data collection was carried out through a questionnaire with a Likert scale, then analyzed using the Partial Least Square (PLS) method through the SmartPLS 3.0 application. The results showed that work professionalism had a positive and significant effect on work discipline and employee performance. Work culture also had a positive and significant effect on work discipline and employee performance. In addition, work discipline was proven to have a positive and significant effect on employee performance. Other findings showed that work professionalism and work culture influenced employee performance through work discipline as a mediating variable. These results indicate that increased professionalism and a positive work culture will foster work discipline, ultimately improving overall employee performance. Therefore, agency leaders need to continue fostering professionalism and a positive work culture by improving competency, discipline, and consistently implementing work values ​​within the organization.